Optimalisasi Kapasitas Trafik Dengan Transceiver Group Synchronization Di PT Xl Axiata Tbk Purwokerto - Alfin Hikmaturokhman; Anggun Fitrian Isnawati; Febry Setyadillah (JURNAL INFOTEL, 2011)
Growth of consumer of peripatetic telecommunications of cellular GSM claims the existence of optimal capacities of traffic to be including maximum customer. One of the improving capacities of traffic by Transceiver Group Synchronization that is merger two Radio Bases of Station or more become one Site. Conducted by Transceiver Group Synchronization will improve capacities of Traffic Channel (TCH) Availability, TCH Traffic, Stand Alone Dedicated Control Channel (SDCCH), degrading TCH Assignment Drop Call and of TCH Congestion Ratio. Herewith will improve Handover Success Ratio (HOSR) and of saving usage of Transceiver Unit (TRU).